Traffic Related Aerosol Exposure And Their Risk Assessment Of Associated Metals In Delhi, India - Kushwaha, Rajesh; Hazarika, Naba; Srivastava, Arin (International Journal of Environment, 2013)
A pilot study was carried out in New Delhi, India, to assess the level of traffic related aerosol exposure, individually and associated metals. These investigations also try to formulate their risk assessment using different modes of transport on a typical journey to work route and compared Bus, Auto-rickshaws and Bike (Two Wheelers) during the journey. The inhalable particulate matter monitored in winter period and also evaluated the potential health risk due to inhalation in the study. The exposure of Particulate matter was observed maximum in the Bike (502 ± 176.38 μgm-3) and minimum in the Auto-rickshaw (208.15 ± 61.38 μgm-3). In case of human exposure to metals (viz. Cu, Cd, Mn, Pb, Ni, Co, Cr, Fe, Zn), it was mostly exposed by Fe, Zn and Co and least exposed by Cd, Cr and Pb. Human health risk was estimated based on exposure and dosage response. The assessment of particulate-bound elements was calculated by assuming exposure of 6 h. The findings indicated that the exposure to particulate bound elements have relatively more adverse health effects. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 26-36 DOI: http://dx.doi.org/10.3126/ije.v2i1.9205